(untitled) (Orinoquia, 2016)
In order to evaluate the effects of larval density rearing on body weight and survival of larvae of striped catfish (Pseudoplatystoma sp), was designed and built a closed recirculation system, which allowed maintaining stable physical and chemical variables of water throughout the experimental period. For this purpose, vitelline larvae were rearing in three densities: 10 (T1), 50 (T2) and 100 (T3) larvae per liter and monitored until 20 days post-hatch. They were evaluated four replicates per treatment, kept under photoperiod 0:24 (light: dark) and fed to apparent satiety with Artemia saline hatchlings, which were supplied divided into five portions a day: at 07:00, 09: 00, 14:00, 18:00 and 22:00 hours. The water quality characteristics observed during the test were: dissolved oxygen 5.7 ± 0.5 mg/L; temperature 26 ± 0.8 ° C; pH 7.6 ± 0.2; hardness 38.2 ± 5.2 mgCaCO3/L; alkalinity 26.5 ± 5.2 mg CaCO3 / L; NH3 <0.02 mg/L; salinity 0.4 ± 0.1 g/L; conductivity 841.1 ± 38.1µS/ cm. At the end of the test, body weight varied inversely with rearing density: 103.0 ± 15.6; 76.1 ± 19.8 and 66.7 ± 9.3 mg, respectively, but no significant difference between the two highest densities P>0.05) were observed. Survival was higher in the density of 10 larvae/L, being statistically different between treatments (86.5 ± 1.9%, 54.7 ± 2.2% and 46.9 ± 3.1% for 10, 50 and 100 larvae/L, respectively, P<0.01). In conclusion, larval density inversely rearing affects body weight and survival of the larvae in this species. Keywords: body weight; density; fish larvae; Pseudoplatystoma sp; survival (Source: AIMS).